Nutritional Investigation, LC-MS-Based Phytochemical Profiling, and Antioxidant Assay of Two Edible Flowers - Kuswati, Kuswati; Zahro, Aliza; Daud, Nadhiratuzzahra Alifiah; Narulita, Erlia; Fatmawati, Yayuk (Bogor Agricultural University, Indonesia, 2026)
Two commonly consumed, yet under-researched, edible flowers—Malvaviscus arboreus (Topi Turki) and Acmella paniculata (Jotang)—were comprehensively analyzed to assess their potential as functional food sources. This study investigated their nutritional content, phytochemical profiles, antioxidant activity, and organoleptic properties. Our methodology, conducted between July and December, 2024, involved a multi-faceted approach—proximate analysis quantified ash, moisture, protein, fat, fiber, carbohydrates, and total energy. Freeze-dried samples underwent LC-MS for phytochemical identification, and antioxidant activity was determined using the DPPH assay. Organoleptic preferences were evaluated through a hedonic test where 30 panelists rated color, aroma, taste, and overall acceptance. Key findings revealed distinct differences. A. paniculata presented higher protein (18.75%), fat (21.71%), and fiber (24.10%), leading to a greater total energy (213.84 kcal/50g). In contrast, M. arboreus showed higher moisture (21.22%) and carbohydrates (48.12%). Phytochemical profiling by LC-MS indicated that M. arboreus contained 51 phytochemicals, primarily phenolics (13.52%), while A. paniculata had a remarkable 170 phytochemicals, dominated by alkaloids (2.94%). Importantly, M. arboreus demonstrated superior antioxidant activity (IC50 92.74 µg/mL, strong) compared to A. paniculata (IC50 156.95 µg/mL, weak) in the DPPH assay. Organoleptically, M. arboreus was preferred for its color, taste, and overall acceptability, with no significant difference in aroma. Overall, both M. arboreus and A. paniculata exhibit promising nutritional value and bioactive potential for functional food applications. This research highlights the significant potential of these edible flowers to diversify plant-based diets and contribute to the development of novel health-promoting products. Future research should focus on optimizing processing techniques and exploring diverse food applications to maximize their utilization.